Effect of pre-exercise carbohydrate ingestion on plasma cytokine, stress hormone, and neutrophil degranulation responses to continuous, high-intensity exercise - Lancaster, G. I.; Jentjens, R. L. P. G.; Moseley, L. (International Journal of Sport Nutrition and Exercise Metabolism, 2003)
The purpose of the present study was to examine the effect of pre-exercise carbohydrate (CHO) ingestion on circulating leukocyte numbers, plasma interleukin (IL)-6, plasma cortisol, and lipopolysaccharide (LPS)-stimulated neutrophil degranulation responses in moderately trained male cyclists who completed approximately 1-h of high-intensity cycling. The influence of the timing of pre-exercise CHO ingestion was investigated in 8 subjects who consumed 75 g CHO as a glucose solution at either 15 (-15 trial), or 75 (-75 trial) min before the onset of exercise. The influence of the amount of pre-exercise CHO ingestion was investigated in a further 10 subjects who consumed either 25 g or 200 g CHO as a glucose solution or a placebo 45 min before the onset of exercise. At the onset of exercise in the timing experiment, the plasma glucose concentration was significantly (p < .05) lower on the -75 trial compared with pre-drink values, and the plasma cortisol concentration and neutrophil to lymphocyte (N/L) ratio were significantly (p < .05) elevated in the post-exercise period. In the -15 trial, plasma glucose concentration was well maintained, and the plasma cortisol concentration and N/L ratio were not significantly elevated above resting levels. However, LPS-stimulated neutrophil degranulation was similar in the -15 and -75 trials. The amount of CHO ingested had no effect on the magnitude of the rise in the N/L ratio compared with placebo when consumed 45 min pre-exercise. Finally, although an exercise-induced increase in the plasma IL-6 concentration was observed, this effect was independent of pre-exercise CHO ingestion.